Characterization of Urinary N-acetyltaurine as a Biomarker of Serum Acetate in Experimental Animal Models of Hyperacetatemia. (29th May 2020) - Mao, Qingqing; Chen, Dongxiao; Shi, Xiaolei; Lu, Yuwei; Yao, Dan; Chen, Chi
Abstract: Objectives: Acetate is an intermediate metabolite originated from multiple important metabolic pathways. Even though blood acetate level has been associated with many health events, it is not commonly monitored in clinical practice, partially due to the needs for invasive blood collection and the challenges in acetate analysis. N -acetyltaurine (NAT) was earlier identified as a novel urinary metabolite of ethanol from the reaction between taurine and ethanol-derived acetate. As a direct metabolite of acetate, NAT has the potential to function as a urinary biomarker that reflects the acetate level inside the body. To test this hypothesis, this study examined the correlations between serum acetate level and urinary NAT level in three experimental animal models of hyperacetatemia. Methods: Glycerol-triacetate (GTA) dosing, ethanol dosing, and streptozotocin (STZ)-induced Type 1 diabetes were used to achieve hyperacetatemia in mice. In GTA model, serum samples were collected at 2 h and urine samples were collected for 24 h after dosing the mice with 5.8 g/kg GTA. In ethanol dosing, serum were collected at 2 h after intraperitoneal injection of 4 g/kg ethanol, while 24 h urine samples were collected before and after 14-day feeding of modified semi-solid diet containing 2.2%–6.7% (v/v) ethanol. In the Type I diabetes model, urine and serum samples were collected before and 5 days after the intraperitoneal injection of 180 mg/kg STZ. The concentrations of NAT and creatinine in urine, as well as acetate in serum, were measured using their respective liquid chromatography-mass spectrometry (LC-MS) methods. Results: The occurrence of hyperacetatemia in three animal models was confirmed by the clear elevation of serum acetate concentrations. The concentrations of urinary NAT were also dramatically increased in three animal models, suggesting the correlations between serum acetate and urinary NAT. Conclusions: Urinary NAT is an effective metabolic marker of hyperacetatemia in three experimental models. The results warrant further investigation on its application in other pathophysiological conditions and in humans. Funding Sources: This research was partially supported by the Agricultural Experiment Station project MIN-18–125 (C. C.) from the United States Department of Agriculture (USDA).